Evaluation of the Stripping Performance of Monochlorotriazine/Vinyl Sulphone Reactive Dyes with a Reductive Stripping Agent - Mahfuza Pervin; Sanjida Sultana; Fahmida Faiza Fahmi; Zinia Yasmin; Sushama Saha Swati (Tekstilec)
The wet processing industry experiences various problems, such as the faulty and uneven shade of dyeing, colour patch formation on the surface of dyed fabric, etc. during the dyeing and subsequent processing of textile materials. Stripping is considered a process that helps to reuse faulty dyed fabrics by minimizing dyeing faults. The aim of this paper is to evaluate the effectiveness of stripping agents and the quality of stripped cotton knit fabrics that were coloured using bi-functional (monochlorotriazine/vinyl sulphone) reactive dyes. First, the trichromatic combination of Drimarene Yellow CL2R, Drimarene Red CL5B and Drimarene Blue HFRL dyes was used to dye fabrics in two different shade percentages, namely light shade (0.3% owf) and dark shade (3.0% owf). Consequently, stripping was carried out using varying concentrations of stripping chemicals (hydrose (Na2S2O4) and caustic soda (NaOH)) and process temperatures. Stripped fabrics were assessed after measuring the weight loss percentage, strength loss percentage, whiteness index and stripping efficiency. The results of that assessment showed a relatively better stripping performance with the chemical concentration of 5 g/L hydrose and 5 g/L caustic soda at 100 °C. Under this condition, the value of the whiteness index and stripping efficiency were adequate, with a minimum weight loss percentage and strength loss percentage. The stripping performance for the light shade (0.3% owf) fabric was deemed to be better than that for the dark shade (3.0% owf) fabric.